Antiangiogenic effects of N6‐isopentenyladenosine, an endogenous isoprenoid end product, mediated by AMPK activation. Issue 3 (21st November 2013) - Pisanti, Simona; Picardi, Paola; Ciaglia, Elena; Margarucci, Luigi; Ronca, Roberto; Giacomini, Arianna; Malfitano, Anna Maria; Casapullo, Agostino; Laezza, Chiara; Gazzerro, Patrizia; Bifulco, Maurizio
Abstract : N6‐isopentenyladenosine (iPA), an end product of the mevalonate pathway with an isopentenyl chain, is already known to exert a suppressor effect against various tumors. In this work, we investigated whether iPA also directly interferes with the angiogenic process, which is fundamental to tumor growth and progression. To this end, using human umbilical vein endothelial cells (HUVECs) as a suitable in vitro model of angiogenesis, we evaluated their viability, proliferation, migration, invasion, tube formation in response to iPA, and molecular mechanisms involved. Data were corroborated in mice by using a gel plug assay. iPA dose‐ and time‐dependently inhibited all the neoangiogenesis stages, with an IC50 of 0.98 μM. We demonstrated for the first time, by liquid chromatography–coupled tandem mass spectrometry (LC‐MS/MS), that iPA was monophosphorylated into 5′‐iPA‐monophosphate (iPAMP) by the adenosine kinase (ADK) inside the cells. iPAMP is the active form that inhibits angiogenesis through the direct activation of AMP‐kinase (AMPK). Indeed, all effects were completely reversed by pretreatment with 5‐iodotubercidin (5‐Itu), an ADK inhibitor. The isoprenoid intermediate isopentenyl pyrophosphate (IPP), which shares the isopentenyl moiety with iPA, was ineffective in the inhibition of angiogenesis, thus showing that the iPA structure is specific for the observed effects. In conclusion, iPA is a novel AMPK activator and could represent a useful tool for the treatment of diseases where excessive neoangiogenesis is the underlying pathology.—Pisanti, S., Picardi, P., Ciaglia, E., Margarucci, L., Ronca, R., Giacomini, A., Malfitano, A. M., Casapullo, A., Laezza, C., Gazzerro, P., Bifulco, M. Antiangiogenic effects of N6‐isopentenyladenosine, an endogenous isoprenoid end‐product, mediated by AMPK activation. FASEB J. 28, 1132–1144 (2014). www.fasebj.org